Comprehensive analysis of the nonperforming household mortgage portfolio using micro-level data - Bálint Dancsik; Gergely Fábián; Zita Fellner; Gábor Horváth; Péter Lang; Gábor Nagy; Zsolt Oláh; Sándor Winkler (Magyar Nemzeti Bank, 2015)
The high ratio of loans over 90 days past due, i.e. nonperforming mortgage loans, is the legacy of the crisis and the excessive lending that preceded it. The volume has continuously grown over the past six years and by the end of 2014 accounted for one quarter of the total mortgage portfolio, affecting approximately 140,000 debtors. The degree of exposure within the entire system of financial intermediation is nearly HUF 1,450 billion, nearly 5 per cent of GDP. Terminated contracts now account for over half of the total portfolio, which may essentially lead to execution and thus the loss of the property for debtors. As a result, this is currently one of the most pressing issues for financial stability and a major social risk in Hungary. A deep analysis and broad understanding of the issue is indispensable for finding the proper solution. Despite the importance of the matter, we know little about nonperforming mortgage loans. This study aims to provide a comprehensive picture of the attributes of these loans after settlement and forint conversion on the basis of individual data. The data clearly show that the heart of the matter in terms of both wealth and income is the excessive level of debt. For over 80 per cent of customers, the total debt amount (outstanding principal and arrears) exceeds the advanced loan amount. Since the onset of the crisis, the amount of principal debt has increased substantially compared to the real estate collateral pledged, currently amounting to 110 per cent on average or 140 per cent if we calculate the indicator based on total debt. The severity of the issue is further exacerbated by the fact that 70 per cent of nonperforming debtors live in smaller cities and localities, primarily in regions where the marketability of properties is limited. As a result, the prospects of a new start after selling the collateral may be limited for debtors. In examining nonperforming loan transactions, it is also essential to analyse income positions in depth, mainly in light of the potential rectification of the loan transactions through sustainable restructuring ...
Keywords: 330